EFFECTIVENESS OF INTEGRATED SOCIAL WELFARE DATA CONTROL (DTKS) IN REALIZED TARGETED FOOD ASSISTANCE IN SOUTH LIKUPANG DISTRICT, NORTH MINAHASA REGENCY - Shylvia Ch. Rumimpunu; Jetty E. H. Mokat; Steven V. Tarore (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effectiveness of Integrated Social Welfare Data (DTKS) control in realizing targeted food assistance in South Likupang District, North Minahasa Regency. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation studies of key informants, then analyzed using the Miles and Huberman interactive model. The results of the study indicate that: (1) in the data updating and recipient suitability indicators, DTKS control has not been running effectively because the updating process is static, incidental, and dependent on a central database, so that field verification tends to be subjective and minimal community participation; (2) in the inhibiting factor indicator, technical obstacles were found in the form of the lack of integration of the village information system with the SIKS-NG application, minimal operator training, and limited digital infrastructure, as well as managerial obstacles that include weak cross-agency coordination, non-standardized distribution procedures, informal intervention by local figures, and the absence of a verified backup data mechanism. Based on these findings, it is recommended that data updates be conducted routinely and in a participatory manner, that digital capacity and human resources of civil servants be improved, that distribution procedures be standardized, and that a coordination forum and transparency of backup data be instituted to ensure accuracy of targeting.